KONSELING PASTORAL: FUNGSI MENDAMAIKAN & MENGUTUHKAN PADA ADAT POTONG TAMO di TAGULANDANG - Brayen Vicard Bulamei; Ivane Dear Suryani Brek (PT. GIAT KONSELING NUSANTARA, 2024)
The purpose of this research is to describe the value contained in the traditional cutting of tamo which has pastoral counseling value in it has elements of reconciling and needing functions that can be used as part of the pastoral counseling method of the Sangir tribe community, especially those in Tagulandang. This research is a qualitative research with descriptive method conducted in Tagulandang in 2024. All data in this study were collected through observation and interviews and documentation studies. From the results, the Tamo custom in Tulude which contains pastoral counseling values by prioritizing the function of reconciling or repairing good relationships spiritually with God as the owner of life, between fellow humans. Tamo contains counseling values that regulate the life journey of the whole community to live in togetherness, equality, unity, and determination to support each other so that the community has a cultural foundation value that serves to help get through various life problems. The function of Mengutuhkan in the Tamo cutting custom is as part of the function applied in pastoral counseling which emphasizes the holistic development of life in all aspects of human life.